The influence of present-day regional surface mass balance uncertainties on the future evolution of the Antarctic Ice Sheet - C. Wirths; C. Wirths; T. F. Stocker; T. F. Stocker; J. C. R. Sutter; J. C. R. Sutter (The Cryosphere, 2024)
Rising global sea levels are one of many impacts associated with current anthropogenic global warming. The Antarctic Ice Sheet (AIS) has the potential to contribute several meters of sea level rise over the next few centuries. To predict future sea level rise contributions from ice sheets, both global and regional climate model (RCM) outputs are used as forcing in ice sheet model simulations. While the impact of different global models on future projections is well-studied, the effect of different regional models on the evolution of the AIS is mostly unknown. In our study, we present the impact of the choice of present-day reference RCM forcing on the evolution of the AIS. We used the Parallel Ice Sheet Model (PISM) to study the AIS in a quasi-equilibrium state and under future projections, combining present-day RCM output with global climate model projections. Our study suggests differences in projected Antarctic sea level contributions due to the choice of different present-day surface mass balance (SMB) and temperature baseline forcings of 10.6 mm in the year 2100 and 70.0 mm in 2300 under the RCP8.5 scenario. Those uncertainties are an order of magnitude smaller than what is estimated from uncertainties related to ice sheet and climate models. However, we observe an increase in RCM-induced uncertainties over time and for higher-emission scenarios. Additionally, our study shows that the complex relationship between the selected RCM baseline climatology and its impact on future sea level rise is closely related to the stability of West Antarctic Ice Sheet (WAIS), particularly the dynamic response of Thwaites and Pine Island glaciers. On millennial timescale, the choice of the RCM reference leads to ice volume differences up to 2.3 m and can result in the long-term collapse of the West Antarctic Ice Sheet.